Increased Engagement or Reduced Exhaustion: Which Accounts for the Effect of Job Resources on Salesperson Job Outcomes? - Matthews, Lucy M.; Zablah, Alex R.; Hair, Joe F.; Marshall, Greg W. (Journal of marketing theory and practice, 2016)
Given the stressful nature of sales jobs, research has historically emphasized the importance of reducing exhaustion for promoting desired salesperson job outcomes. Building on data provided by 235 B2B salespeople, this study finds that while reducing exhaustion is important, enhancing engagement may be more critical. Specifically, the results reveal that engagement mediates the effects of customer orientation, training, and supervisor support on sales performance, but exhaustion does not. Furthermore, the results indicate that exhaustion and engagement both mediate the effects of supervisor support on turnover intentions. Implications of the study's findings for theory and practice are discussed.